STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN PADA BUDIDAYA JAMUR TIRAM PUTIH DI DESA ALAS NYIUR KECAMATAN BESUK - Fithri, Naylal; Muhammad Rofek (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2023)
White oyster mushroom is one of the vegetable commodities that can be used for food and nutraceuticals (food and beverages for the prevention and treatment of disease). Mushroom cultivation has bright prospects in Indonesia because of the very supportive natural conditions, besides that, the raw materials for making substrates or mushroom planting logs are quite abundant. The purpose of this research is to find out and analyze the marketing strategy of oyster mushrooms in Alas nyiur village, Besuk sub-district. This research method uses a qualitative method with a case study research approach to describe the research objectives of the marketing strategy of oyster mushrooms in the village of Alas nyiur, Besuk. The focus raised in this research is in the village of Alas nyiur, Besuk sub-district, Probolinggo district. This research was conducted by conducting observations and interviews (collecting data from the field). the beginning of the establishment of the white oyster mushroom business Zainal attended training from the village on white oyster mushroom cultivation, after attending the training Zainal tried to apply the knowledge he got from the training about white oyster mushroom cultivation in his own village. started the white oyster mushroom business in the village of alas nyiur on January 10, 2020, which is a white oyster mushroom cultivation business initiated by Zainal's brother. the strategy used is to look for people who are baskets / collectors of white oyster mushrooms themselves, after we got information that that person is a collector of white oyster mushrooms and is also ready to supply every day, after that I offer white oyster mushrooms which I have white oyster mushroom collectors.